Role of apoptosis factors during mouse neural stem cell differentiation - Aranha, Márcia Maria de Almeida, 1980- (2010)
Tese de doutoramento, Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2010